(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2024)
Public policy of securing juvenile rights today has been designated as one of the priority tasks at the level. Notable is the basis of all the tasks set, and above all, human right unconditional provision of guarantees of protection, the rule of law.